Implementasi Perubahan dan Pengembangan Organisasi SMK Pertanian Kabupaten Pasaman Barat - Suatrina, Yenita; Wesmi, Wesmi; Asmendri, Asmendri; Sari, Milya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to investigate the implementation of change and organizational development in the Agricultural Vocational High School (SMK Pertanian) of Pasaman Barat Regency. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentary studies. The research population includes all stakeholders related to the Agricultural Vocational High School, while the research sample is selected using purposive sampling technique. The results of the study show that the implementation of change and organizational development in the Agricultural Vocational High School of Pasaman Barat Regency has had a significant impact, especially in improving the quality of education and services to students. Several success factors in the implementation of change include the commitment of school leaders, active participation of all members of the organization, and solid support and cooperation among the school, parents of students, and other relevant parties. The implications of these findings emphasize the importance of continuously developing strategies and programs to improve the quality of education in the Agricultural Vocational High School of Pasaman Barat Regency, focusing on aspects of leadership, organizational member participation, and cross-stakeholder cooperation